Pathological manifestations in a historic building: post-fire scenario at Casarão dos Fabricantes - Bezerra, Maria Helena C. M.; Lima, Lorrayne Silveira; Lavor Magalhães, Ana Livia; Filho, Lauro Santos; Miyasaki, Julia Santos; Carvalho, Elayne Valério (Revista ALCONPAT, 2024)
The objective of this study is to document the pathological manifestations of the Casarão dos Fabricantes, one of the oldest buildings in Fortaleza, which was severely damaged by a major fire in 2020. Despite its historical significance, there are no records detailing the condition of the building either before or after the fire. The internal walls and two facades were the only construction elements that were not destroyed by the fire. The survey of the pathological manifestations was conducted by visual assessment and infrared thermography, revealing different degradation processes across the evaluated structures and providing a systematic view of the extent of the damage to the building. Mapping this damage provided an integrated approach, offering a scientific basis to support the restoration process.